PENGARUH MODAL INTELEKTUAL DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS BANK UMUM SYARIAH (STUDI PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2013-2017) - Maqfirah, Sarah; Fadhlia, Wida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This study aims to (1) To determine the effect of intellectual capital on the profitability of Islamic commercial banks, (2) To determine the effect of company size on the profitability of Islamic commercial banks. (3) To determine the effect of intellectual capital and company size together on the profitability of a Sharia Commercial Bank. The population in this study were 14 Islamic commercial banks in Indonesia. The sampling technique in this study used purposive sampling technique. This study is a study that uses secondary data for research. Secondary data in the form of annual reports and financial reports obtained on the website of each Islamic commercial bank. The conclusions resulting from this study are (1) Intellectual capital affects the profitability of Islamic commercial banks, (2) Firm size influences the profitability of Islamic commercial banks, (3) Intellectual capital and company size together influence profitability.